2019
DOI: 10.12911/22998993/111463
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Anthropogenic Environment – Permanent Puddle as a Place for Development of Diatoms

Abstract: Specific conditions in urban areas favour large species richness, these are also places prone to the anthropogenic pressure. As a result, many studies on aquatic habitats in urban ecosystems have been carried out. The aim of this study was to investigate the diversity of diatom assemblages developing in artificial environment in relation to water chemical parameters. The study was performed on a small water outflow in south-eastern Poland, which started in the storm sewage. The water at the studied sites was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The high abundance of Diatoms in the two ponds despite their low motility could be explained by the cosmopolitan nature of these organisms with a strong capacity to adapt to variations of environmental conditions and to various environments. Their distributions throughout the water column are related to winds and rains that generate strong turbulence, allowing the resuspension of Diatoms and other algae that tend to sink because of their densities, which are always slightly higher than the water, and to be found in the euphotic zone when they are below [29]. The high abundance of Chlorophyceae is explained by the very high levels of nitrogen elements recorded during the study period, making this nutrient the limiting factor in all the ponds studied.…”
Section: Phytoplankton Dynamicsmentioning
confidence: 99%
“…The high abundance of Diatoms in the two ponds despite their low motility could be explained by the cosmopolitan nature of these organisms with a strong capacity to adapt to variations of environmental conditions and to various environments. Their distributions throughout the water column are related to winds and rains that generate strong turbulence, allowing the resuspension of Diatoms and other algae that tend to sink because of their densities, which are always slightly higher than the water, and to be found in the euphotic zone when they are below [29]. The high abundance of Chlorophyceae is explained by the very high levels of nitrogen elements recorded during the study period, making this nutrient the limiting factor in all the ponds studied.…”
Section: Phytoplankton Dynamicsmentioning
confidence: 99%
“…Pinnularia cuneola is mentioned in the taxa lists from Romania (Caraus 2017) and the Netherlands (Veen et al 2015). It was also found in a small puddle in Stalowa Wola (Rybak et al 2019). Until now, the species has not been reported in soils, and studies have shown that it can also develop in this habitat, especially on sthe oils covered with mosses.…”
Section: Discussionmentioning
confidence: 99%
“…Since Xiao-li et al [5], research on spider webs have been conducted in Poland by Rybak at al. and focused mainly on road traffic emissions [7][8][9][10][11]. Rybak investigated cumulative ability of spider webs to heavy metals across Wrocław, Lower Silesia.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…They are commonly found in urbanized areas like road tunnels, bridges, parking lots and homesteads. Webs of Agelenidae, Pholcidae and Linyphiidae family proved to be excellent bioindicators of atmospheric pollutants [7][8][9][10][11].…”
Section: Heavy Metalsmentioning
confidence: 99%